Clinical, pathological and radiological profile of sinonasal masses in patients presenting to a tertiary care center: a retrospective observational study - Bhalodiya, Neena; Prajapati, Kerul J.; Hingol, Parth; Bhadania, Simple (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The study aimed to assess the profile of various pathological conditions that present with nasal mass in Indian patients. Methods: This is a retrospective observational study of 43 patients of sinonasal masses who visited GMERS Medical College and Hospital, Sola, Ahmedabad, India during May 2017 to March 2020. The clinical profile of sinus or nasal masses were observed along with their radiological features on computed tomography scans of paranasal sinuses. The age and gender sub group were also assessed for distribution of these conditions. Most of the patients were managed with surgical techniques. Results: Overall, clinical profile of 43 patients was observed. The clinicopathological examination aided by endoscopic and imaging studies revealed that 20 (46.5%) patients presented with the non-neoplastic masses and remaining were with neoplastic masses (53.5%). The overall M: F ratio was 1.5:1. Most of the patients belong to 11-30 years age group. The most common symptoms were mass in the nasal cavity and nasal discharge. Polyps were most common lesions seen (25.6%). Surgical intervention in the form of biopsy, excision of mass, functional endoscopic sinus surgery was performed in all patients. Conclusions: This study gives an insight into various lesions presenting as sinonasal masses and their clinical and pathological profile. Overall, surgical management in form of excision by endoscopic or external approach is effective modality of treatment supplemented with appropriate medical management.